Pengaruh Self Esteem, Self Efficacy Dan Penghargaan Terhadap Kepuasan Kerja Karyawan Di Pt. Pos Indonesia (Persero) Probolinggo - Pratiwi, Silfi Ajeng; Bahri, Mohammad Saiful; Nafis, Raihan Wishal (JUMAD : Journal Management, Accounting, & Digital Business, 2024)
This research was conducted at PT. Pos Indonesia (Persero) Probolinggo with the research objective to be achieved is to determine the influence of Self Esteem, Self Efficacy, and Rewards and Partial Employee Job Satisfaction at PT. Pos Indonesia (Persero) Probolinggo. During the time the researcher conducted the research, the sample taken was 44 respondents using the sampling technique, namely incidental sampling technique. The type of research used in this research is quantitative descriptive research, the variables used include Self Esteem, Self Efficacy, Reward and Employee Job Satisfaction. The data analysis method from the results of this research is a quantitative descriptive method using statistics in the form of instrument tests, normality tests, reliability tests, classical assumption tests, multiple linear regression analysis, coefficient of determination and partial hypothesis testing (t test). The research results are shown by the results of a partial hypothetical test that has been carried out with a significance level of 5%. It can be concluded that 1) Self Esteem with a tcount value of 3.606 is greater than ttable 1.683. 2) Self Efficacy with a tcount value of 2.484 is greater than ttable 1.683. 3) The award with a tcount value of 3,892 is greater than ttable 1,683.